Forms of Violence by Sabaot Land Defence Force and its Effects on the Wellbeing of Women in Kopsiro Division, Mt. Elgon, Kenya - Chemegemet, R. M.; Njonge, T.; Omulema, B. (Africa Environmental Review Journal, 2021)
The World Health Organization’s (WHO) report in 2014 indicates that approximately 1.4 million lives are lost every year as a result of violence. Even more people are injured and suffer from a range of physical, sexual, reproductive, and mental health issues with any death caused by abuse, with women being the most vulnerable. This paper addresses the issue of violence as orchestrated by the Sabaot Land Defence Force (SLDF) in Kopsiro division of Mount Elgon sub-county. Four objectives guided the study. Establishing the forms of violence employed by the SLDF, identifying the effects of the SLDF violence on the women’s psychosocial wellbeing, determining the coping strategies adopted by the women as victims of the SLDF violence and finding out the role of counselling in helping the women deal with post-traumatic effects of the SLDF violence. The study was carried out among women groups in Emia, Chepyuk, Kapkateny and Chongeywo locations in Kopsiro division and adopted ex post facto design. Targeting a population of 23,852 women in the region, 690 women were accessible from which forty (40) were selected through purposive sampling technique sixteen (16) of whom were leaders. Each study location therefore produced 10 women. The study used focus group discussions to obtain data from the sampled groups and interview schedule from the selected leaders. A pilot study was conducted in Cheptais division using twenty (20) women from two women groups. A detailed narration of the qualitative data was gathered through Focus Group Discussions (FGDs) and interview schedule were analyzed thematically. The findings of the study revealed that the majority of the women suffered psychologically and socially during the Sabaot Land Defence Force (SLDF) violence. For instance: a number of them experienced stress and some of them developed ulcers, lack of sleep and nightmares. This paper is therefore expected to create more awareness through sensitization of the community on the effects of (SLDF) violence on the women’s psychosocial wellbeing in Kopsiro division of Mount Elgon sub-county.